Study on the Effect of Soft and Hard Coal Pore Structure on Gas Adsorption Characteristics - Xun Zhao; Tao Feng; Ping Wang; Ze Liao (Advances in Civil Engineering)
In order to grasp the effect of soft and hard coal pore structure on gas adsorption characteristics, based on fractal geometry theory, low-temperature nitrogen adsorption and constant temperature adsorption test methods are used to test the pore structure characteristics of soft coal and its influence on gas adsorption characteristics. We used box dimension algorithm to measure the fractal dimension and distribution of coal sample microstructure. The research results show that the initial nitrogen adsorption capacity of soft coal is greater than that of hard coal, and the adsorption hysteresis loop of soft coal is more obvious than that of hard coal. And the adsorption curve rises faster in the high relative pressure section. The specific surface area and pore volume of soft coal are larger than those of hard coal. The number of pores is much larger than that of hard coal. In particular, the superposition of the adsorption force field in the micropores and the diffusion in the mesopores enhance the adsorption potential of soft coal. Introducing the concept of adsorption residence time, it is concluded that more adsorption sites on the surface of soft coal make the adsorption and residence time of gas on the surface of soft coal longer. Fractal characteristics of the soft coal surface are more obvious. The saturated adsorption capacity of soft coal and the rate of reaching saturation adsorption are both greater than those of hard coal. The research results of this manuscript will provide a theoretical basis for in-depth analysis of the adsorption/desorption mechanism of coalbed methane in soft coal seams and the formulation of practical coalbed methane control measures.